2022
DOI: 10.3390/ijerph19031465
|View full text |Cite
|
Sign up to set email alerts
|

An Uninformed Decision-Making Process for Cesarean Section: A Qualitative Exploratory Study among the Slum Residents of Dhaka City, Bangladesh

Abstract: The decision-making process and the information flow from physicians to patients regarding deliveries through cesarean section (C-section) has not been adequately explored in Bangladeshi context. Here, we aimed to explore the extent of information received by mothers and their family members and their involvement in the decision-making process. We conducted a qualitative exploratory study in four urban slums of Dhaka city among purposively selected mothers (n = 7), who had a cesarean birth within one-year prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This inclusion might encompass educating family members on the significance of treatment adherence, accentuating their supportive role, and cultivating an environment conducive to sustained compliance. 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inclusion might encompass educating family members on the significance of treatment adherence, accentuating their supportive role, and cultivating an environment conducive to sustained compliance. 28 …”
Section: Discussionmentioning
confidence: 99%
“…family members on the significance of treatment adherence, accentuating their supportive role, and cultivating an environment conducive to sustained compliance. 28 A noteworthy observation is the consistency in the questions related to the "K" dimension across both patient and family member questionnaires, yet a contrasting positive effect in the SEM results for family members. This intriguing phenomenon warrants in-depth exploration to discern potential reasons behind this positivity among family members, despite the shared questionnaire content.…”
mentioning
confidence: 96%
“…One previous study reported that physicians and the breadwinner of the pregnant woman’s family are the primary decision-makers behind CS delivery and that pregnant women are often excluded from that decision-making process ( 9 ). Thus, women are probably not aware that an unnecessary CS can result in increased risk of infection, potential complications in subsequent pregnancies, and prolonged recovery times ( 10 ). Previous evidence has shown that a combination of sociocultural factors, such as education, social class, and religion, and medical factors, such as pregnant women’s high blood pressure and/or diabetes, contributes to this increasing CS rate ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, they describe ideal situations which require more financial and human resources than are readily available. They call for continuous training by specialists, increasing the financial burden and workload on most hospitals [9]. Finally, the guidelines lack a clear scientific base regarding data sources or human sources responsible for creating them.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed the process of decision-making could impact C-section choice. This process affects by doctors' beliefs of what is supposed medical or medical indications, absences of collective decision between staff as to lack of cooperation among midwives [8] and gynecologists, and maternal requests, and it is a crucial part of women's involvement in the decision-making process [9].…”
Section: Introductionmentioning
confidence: 99%